TENDENCIES OF PLANT PRODUCTION IN THE REPUBLIC OF SERBIA AND AT THE LEVEL NUTS 1 - Grujić, Biljana Lj.; Roljević Nikolić, Svetlana M.; Subić, Jonel V. (Journal of Agricultural Sciences (Belgrade), 2020)
In this paper was analyzed the development of plant production in the Republic of Serbia and at the level of the territorial units Serbia-North and Serbia-South (NUTS 1), for the period 2009-2018 through the indicators of the coverage of areas and average yield of 28 plant crops. For the analysis of the observed indicators, the methods of descriptive statistics as well as Spearman’s correlation coefficient were used. The data indicate that in the region Serbia-North is dominated by areas under cereals, industrial crops, peas and peaches, while in the region Serbia-South is covered by areas under fodder crops, vegetable crops (potatoes, tomatoes, peppers, onion, garlic, beans, cucumber, melons and watermelons) and perennial crops. The average yields of the observed cultures distinguish significantly between the region Serbia-North and Serbia-South. Spearmen’s correlation coefficient of the indicators of the coverage of areas is indicated a high degree of stacking of areas under wheat and tobacco (0.927**), as well as areas under lucerne and clover with areas under fruit plantations. Also, a high degree of stacking of areas under maize and peas (0.798**) was established, but also between areas under sunflower and soya (0.891**). Key words: plant production, crops, utilized land, NUTS 1, indicators.